An Efficient Codification to Solve Distribution Network Reconfiguration for Loss Reduction Problem - Carreno, Edgar Manuel [UNESP]; Romero, Ruben [UNESP]; Padilha-Feltrin, Antonio [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2008)
Evolutionary algorithms have been used to try to solve distribution network reconfiguration for loss reduction problem with a certain degree of success. But some problems, specially related to a codification that is able to represent and work with a complex multiconstraint and combinatorial problem such as this one, have prevented the use of the full potential of these algorithms to find quality solutions for large systems with minor computational effort. This paper proposes a solution to this problem, with a new codification and using an efficient way for implementing the operator of recombination to guaranty, at all times, the production of new radial topologies. The algorithm is presented and tested in a real distribution system, showing excellent results and computational efficiency.
Keywords: Distribution network reconfiguration; genetic algorithms; loss reduction; metaheuristics; network representation